2019
DOI: 10.1101/733212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unexpected sound omissions are signaled in human posterior superior temporal gyrus: an intracranial study

Abstract: Context modulates sensory neural activations enhancing perceptual and behavioral performance and reducing prediction errors. However, the mechanism of when and where these high-level expectations act on sensory processing is unclear. Here, we isolate the effect of expectation absent any auditory evoked activity by assessing the response to omitted expected sounds. Electrophysiological signals were recorded directly from the superior temporal gyrus (STG) and superior temporal sulcus (STS) in patients with medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Intracranial studies in humans confirmed mixed contributions of deviance detection and adaptation to mismatch responses in auditory cortices (Ishishita et al, 2019). Furthermore, such studies provided indications that cortical processing is not spatially homogeneous (Hughes et al, 2001;Flinker et al, 2011;Fonken et al, 2019) and that adaptation and deviance detection responses can be differently distributed (Blenkmann et al, 2019;Ishishita et al, 2019), indicating the existence of specialized, interconnected sub-regions within the auditory stream for the processing of contextual information. Thus, animal studies make it possible to dissect the distinctive contributions of different interneuron populations to networklevel SSA (Natan et al, 2017) and deviance detection mechanisms (Ross and Hamm, 2020) that are likely to underlie similar processes observed in humans.…”
Section: Mmn As a Major Biomarker Of Predictionmentioning
confidence: 92%
“…Intracranial studies in humans confirmed mixed contributions of deviance detection and adaptation to mismatch responses in auditory cortices (Ishishita et al, 2019). Furthermore, such studies provided indications that cortical processing is not spatially homogeneous (Hughes et al, 2001;Flinker et al, 2011;Fonken et al, 2019) and that adaptation and deviance detection responses can be differently distributed (Blenkmann et al, 2019;Ishishita et al, 2019), indicating the existence of specialized, interconnected sub-regions within the auditory stream for the processing of contextual information. Thus, animal studies make it possible to dissect the distinctive contributions of different interneuron populations to networklevel SSA (Natan et al, 2017) and deviance detection mechanisms (Ross and Hamm, 2020) that are likely to underlie similar processes observed in humans.…”
Section: Mmn As a Major Biomarker Of Predictionmentioning
confidence: 92%
“…To our knowledge, only one study using EEG has found what may be an MMN or P3a‐like response to a stimulus using an SOA of 1 s, but the responses were small and variable, limiting the researchers' interpretation of the ERPs (Busse & Woldorff, 2003). However, intracranial recordings (Fonken et al, 2019; Halgren et al, 1995) have found specific responses, including increased high frequency power, to sound omissions, even with SOAs larger than 200 ms. Thus, it remains an open question whether MMN and P3a measured in EEG reflect predictive errors for unexpected omissions.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to a recent study that used relatively low-spatial resolution surface electrodes to measure broad local field potentials in human superior temporal gyrus, which contains higher auditory areas than we typically examined. This study reported neuronal populations that responded only to omitted sounds, but not to presented sounds (Fonken et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Earlier human studies have suggested that omission responses can be observed only for relatively fast stimulus presentation rates, well above 5 Hz (Yabe et al, 1997), which was interpreted as a limited window of temporal integration. However, mounting evidence demonstrates that omission responses can also be observed in awake humans following longer inter-stimulus intervals, in the sub-second (Fonken et al, 2019; Halgren et al, 1995) and supra-second range (Busse and Woldorff, 2003). Omission responses at different time scales may be differentially influenced by cognitive factors: for instance, omissions following short ISIs (periodicity > 5 Hz) have been suggested to be elicited entirely automatically, while slower time scales (periodicity < 2 Hz) may be modulated by attention (Chennu et al, 2016; Chien et al, 2019; Karamürsel and Bullock, 2000), but see (Hughes et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation